MANAGEMENT OF PERSONNEL INITIATIVE AS THE AS THE ACTIVITIES OF THE MODERN ORGANIZATION - I. Esaulova; I. Semenova (Вестник университета)
The urgency of using personal and organizational mechanisms for activating the personnel initiative for the effective functioning and development of the company is determined. The essence of the potential of proactive employee as a source of individual initiative is revealed, the characteristic of its basic elements and forms of manifestation is given. The goals and principles of managing the initiative of personnel are formulated, and the main elements of the organizational environment that facilitate the mobilization of personnel initiatives are identified. The model of personnel initiative management based on mobilization mechanisms, concentrated in the organization management system, human resource management system, as well as specific infrastructural mechanisms, purposefully and consistently providing a positive impact on the potential of proactive employee is presented.